Identification of the pathogenic variants in two Chinese patients with primary ciliary dyskinesia - ZHENG Haixia, ZHOU Wangji, TIAN Xinlun, LIU Yaping (Jichu yixue yu linchuang, 2024)
Objective To characterize the clinical features and to identify the pathogenic variants in two Chinese patients with primary ciliary dyskinesia (PCD). Methods The clinical data and peripheral blood sample from the patients were collected, and genomic DNA was subsequently extracted from the peripheral blood. Candidate pathogenic variants were identified using whole exome sequencing (WES) and further confirmed by Sanger sequencing technology. Finally, the pathogenicity of the variants was predicted through bioinformatic analysis. Results Two Chinese patients with PCD had diffuse bronchiectasis cpmlicated with recurrent infection and the decreased level of nasal nitric oxide (nNO). WES results showed that both patients carried frameshift mutations in known pathogenic genes of PCD. Patient 1 carried a homozygous variant in outer dynein arm docking complex subunit 1 (ODAD1) (NM_144577): c.702_705dupGCAG (p.P236Afs*11) and patient 2 carried a hemizygous variant in dynein axonemal assembly factor 6 (DNAAF6) (NM_173494): c.532_533delCT (p.L178Sfs*2). Neither variant had been recorded in The Human Gene Mutation Database (HGMD). Both frameshift variants caused changes in the open reading frame, which resulted in premature termination codon. According to the American College of Medical Genetics and Genomics (ACMG) guidelines, c.702_705dupGCAG in ODAD1 was categorized as a pathogenic variant (PVS1+PM2+PM3+PP4) and c.532_533delCT in DNAAF6 was categorized as a pathogenic variant (PVS1+PM2+PM3+PP4). Conclusions The novel variants c.702_705dupGCAG found in ODAD1 and c.532_533delCT found in DNAAF6 are pathogenic and support their PCD diagnosis for the two patients, respectively. These results may enrich the mutation spectrum of the ODAD1 and DNAAF6.